2015
DOI: 10.1144/geochem2014-326
|View full text |Cite
|
Sign up to set email alerts
|

Portable X-ray fluorescence measurements on exploration drill-cores: comparing performance on unprepared cores and powders for ‘whole-rock’ analysis

Abstract: One geoscience application of pXRF technology is acquiring 'whole-rock' analyses of unmineralized or weakly mineralized rock cores for major oxides and trace elements, to fill the gaps between traditional laboratory analyses and/or obtain geochemical data more quickly. But the question of whether the samples actually need to be crushed and pulverized before analysis to produce useful results has not been extensively studied. In this paper pXRF data quality is compared on unprepared rock cores and on powders in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…Overall, the analyses of the samples’ surfaces with pXRF provided comparable results with those using ICP‐AES, especially when analysing the fine‐ to medium‐grained volcanic rocks and averaging multiple measurements on different spots of a clean surface of the artefact. These results are in agreement with other assessments of the analytical accuracy of this technique (Bourke & Ross ). However, the analyses of coarse‐grained material and/or weathered surfaces are more divergent (especially in the measurement of MnO, Sr and Y), which is probably related to textural variation and chemical weathering as shown in the online Supporting Information Figure .…”
Section: Methodssupporting
confidence: 92%
“…Overall, the analyses of the samples’ surfaces with pXRF provided comparable results with those using ICP‐AES, especially when analysing the fine‐ to medium‐grained volcanic rocks and averaging multiple measurements on different spots of a clean surface of the artefact. These results are in agreement with other assessments of the analytical accuracy of this technique (Bourke & Ross ). However, the analyses of coarse‐grained material and/or weathered surfaces are more divergent (especially in the measurement of MnO, Sr and Y), which is probably related to textural variation and chemical weathering as shown in the online Supporting Information Figure .…”
Section: Methodssupporting
confidence: 92%
“…For till samples, and Sarala (2016) used three repeated measurements to increase accuracy and to diminish matrix and heterogeneity effects. Bourke and Ross (2016) reported that repeating measurements (3 to 7 times) at the surface of a core produced the same accuracy as milling, for fine to medium-grained metavolcanics.…”
Section: Matrix Heterogeneity Issuesmentioning
confidence: 96%
“…Consequently, critical elements can be detected and reliably quantified in geological materials devoid of interfering elements or when enriched. Generally, pXRF data need to be corrected or re-calibrated to yield accurate results, which is mostly achieved through linear correlation (e.g., [3,5,10,[25][26][27][28]. This is frequently done without checking the energy spectra corresponding to pXRF measurements for spectral interferences and, in particular, for false positives.…”
Section: Introductionmentioning
confidence: 99%